Age Is a Predictor for the Syncope Recurrence in Elderly Vasovagal Syncope Patients With a Positive Head-Up Tilt Test - Guo, Yongjuan; Chen, Xiaomin; Zeng, Tianze; Wang, Lin; Cen, Lvwei (Frontiers in Cardiovascular Medicine, 2021)
BACKGROUND Valid predictors of the syncope recurrence in vasovagal syncope (VVS) patients with a positive head-up tilt test (HUTT) are currently lacking. The goal of this study was to identify the predictive performance of age for the recurrence of syncope in VVS patients with a positive HUTT. METHODS In total, 175 VVS patients with a positive HUTT were observed for 6 to 32 months, and the recurrence of ≥1 syncope or typical pre-syncope prodromal episodes during follow-up was considered syncope recurrence. The population was divided into 2 groups, namely, a syncope recurrence group (44 patients) and a no syncope recurrence group (131 patients). The baseline clinical data, haemodynamic parameters and classification of VVS on the HUTT were analysed. Logistic regression was used to analyse the effect size and confidence interval for age. A receiver operating characteristic (ROC) curve analysis was used to assess the predictive performance and investigate the predictive value of age by the area under the curve (AUC). RESULTS The median age of the syncope recurrence group was older than that of the no syncope recurrence group [60.0 (47.8, 66.0) years>53.0 (43.0, 62.0) years], and there was a significant difference between the two groups (P < 0.05). The trend for syncope recurrence changed with advancing age, and the logistic regression model adjusted by sex showed that older patients had an increased risk of syncope recurrence in VVS with a positive HUTT [OR value: 1.03, 95% confidence interval (CI): 1.008 to 1.061, p < 0.05]. Age was a valid predictor for the recurrence of syncope in elderly VVS patients with a positive HUTT (AUC: 0.688; 95% CI: 0.598 to 0.777, p < 0.05). The cut-off value was 53.5 years, and the sensitivity and specificity were 72.7% and 52.7%, respectively. CONCLUSIONS Age may be a valid predictor for syncope recurrence in elderly VVS patients with a positive HUTT. The rate of syncope recurrence increased with advancing age, especially in females.